Kindness makes us strong - Beer, Sophie (New York, NY : Dial Books for Young Readers, 2019)
Celebrates kindness as it displays various children extending kindness in all kinds of situations, including on the playground, at lunchtime, and on a neighborhood street.
Keywords: Board books; Kindness -- Fiction; Board books